1. Evaluate 3x^2 + 5x - 8 when:
a) x = 2
3(2)^2 + 5(2) - 8
3(4) + 10 - 8
12 + 10 - 8
22 - 8
14
b) x = -3
3(-3)^2 + 5(-3) - 8
3(9) -15 - 8
27 - 15 - 8
12 - 8
4
c) x = 0.62
3(0.62)^2 + 5(0.62) - 8
3(0.3844) + 3.1 - 8
1.1532 + 3.1 - 8
-3.7468
2. Simplify: 4x - 3x^2 + 2x - x^2
collect like terms
4x + 2x - 3x^2 - x^2
6x - 4x^2
2x(3 - 2x)
3. Simpilfy: (5 x 6^2 - 5 x 3^2)/( 3 + 2)
Using BODMAS or PEMDAS
We treat the problems in the brackets first
{(5 x 6^2 - 5 x 3^2)}/(3 + 2)
In here we treat the multiplications first
{(5 X 36) - (5 X 9)}/(3 + 2)
(180 - 45)/5
135/5
= 27
2006-11-12 06:35:37
·
answer #1
·
answered by Loral 2
·
0⤊
2⤋
the first equation would be like this
3x ^ 2 + 5x - 8
a) if x=2 evaluating: 3(2)^2 + 5(2) - 8 or 3*4 + 5(2) -8
=12 + 10 - 8 = 14
b) if x= -3 3(-3)^2 + 5(-3) - 8 or 3(9) -15 - 8
= 27 -15 - 8 = 4
c) if x= .62 3(.62)^2 + 5(.62) - 8 or 3(.3844) + 3.1 - 8
= 1.1532 +3.1 - 8 = -3.7468
then, the 2nd equation would be 4x - 3x^2 + 2x - x^2
by adding the similar terms -4x^2 + 6x
next take the take teh common factor
you will get the answer = -2x (2x - 3)
the third will be [ 5 (6^2) - 5 (3^2) ] / 5
take the common factor of the numerator you will get
5 ( 6^2 - 3^2 ) / 5 then cancel both number 5 in
the numerator and denominator
6^2 - 3^2 will be left
extracting the roots you will get 36 - 9 = 27
2006-11-13 00:30:36
·
answer #2
·
answered by jdash01 3
·
0⤊
0⤋
The first answer has errors that you can learn from.
Please check answers below, compare to the first answer
and make sure you recognize common mistakes so you know the difference.
1). Evaluate means to plug in the "number" given for each x.
To show your steps where you can check your work more easily,
I would put (2) in parentheses, or (-3) or (.62) in place of x.
a) 3*(2)^2 + 5(2) - 8
b) 3*(-3)^2 + 5(-3) - 8
c) 3*(.62)^2 + 5(.62) - 8
Simplify means to combine like terms, so adding or subtracting all "x" together, all "x^2" together, and all constants together.
2) check again
4x - 3x^2 + 2x - x^2
(4x + 2x) - 3x^2 - x^2
6x - 4x^2 or
- 4x^2 + 6x
3) check again
(5 * 6^2 - 5 * 3^2) / (5)
5 x (36 - 9) / 5
cancel the 5 on top and bottom
36 - 9 = 27 not 21
You be the teacher.
Check these answers again and correct any errors.
I used * for multiplication
^ for squared
/ for division
2006-11-12 06:15:42
·
answer #3
·
answered by emilynghiem 5
·
0⤊
0⤋
apparently your teacher isnt very good because this is 8th grade material for me. for #1 just plug in a,b, and c. and factor and use gcf for 2 and 3. i wont answer them for you but im more than happy to tell you how to do them.
1a.} plug in 2. [3(2)]squared. +5(2) -8
1b.} [3(-3)]squared. +5(-3) -8
1c.} [3(.62)] squared. +5(.62) -8
for 1abc, the brackets means that you multiply then square the product.
2. all you ahve to do is take out a gcf. the one thing that all of these have in common is an x. so if you take an x out then the quotient will be x(4-3x+2-x). add the like terms together and factor. x(2x+6). you can now take another thing out. that is a 2. it will now be 2x(x+3). and there is your answer.
3. just do the math. its very simple 6th grade material. (5 x 6squared - 5 x 3squared) divided by (3+2). okay well what your going to do is work out ever little piece. the first piece, 5 x 6 squared, you will first find 6 squared which you should know is 36. multiply 5x36=180. now do the second piece on your own. then the bottom piece which is 3+2 and you really should know 3+2=5. then subtract the first two pieces divide the bottom piece and poof. you have an answer
2006-11-12 06:11:16
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
3x^2 + 5x - 8
3(4)+5(3)-8 = 12 +15 - 8= 27 - 8 =19
3(9)+5(-3)-8 = 36-15-8 = 21-8 = 14
3(.3844)+5(.62)-8 = 1.1532 + 3.1 - 8 = 4.2532 - 8 = -4.2832
4x - 3x^2 + 2x - x^2
combine like terms 3x^2-x^2 = 2x^2 and 4x+ 2x = 6x
simplified 2x^2+6x
5 * 6^2 - 5 * 3^2 / 3+2
5(6^2) - 5(3^2)/5 = 180-45/5 = 135/5 = 27
2006-11-12 07:58:54
·
answer #5
·
answered by ikeman32 6
·
0⤊
0⤋
Hello Dear advisor ;
● Part ONE ;
3 x^2 +5x - 8 =0
a) x = 2
3 ( 2^2) + 5(2) - 8 = 12 + 10 - 8 = 14
b) x = -3
3 ( -3^2) + 5(-3) - 8 =27 -15 - 8 = 4
c) x = 0.62
3 ( 0.62^2) + 5(0.62) - 8 = 1.1532 + 3.1 -8 = -3.7468
● Part TWO ;
4x - (3x)^2 + 2x - (x)^2
4x - 9x^2 + 2x - x^2
4x - 9x^2 + 2x - x^2
6x - 10x^2
Factor " 2x "
2x ( 3 - 5x)
● Part THREE
5x ^ 6 - 5x ^3 / ( 3 +2)
5 (x^ 6) - 5(x^3) / (5)
Factor " 5 " & " x^3 "
(5x^3)(x^3 - 1)/ 5
Cancel " 5 "
x^3(x^3 - 1)
Good Luck Darling
{ goodness me if for Part 3 you meant (5 * 6^2 - 5*3^2) / 3+2
6 ^2 = 36
3 ^2 = 9
(5*36 - 5 * 9) / 5
Factor 5
5( 36 - 9 ) / 5
Cancel 5
35 - 9 = 27 } ....
2006-11-12 06:36:42
·
answer #6
·
answered by sweetie 5
·
3⤊
0⤋
3x² + 5x - 8
3(2)² + 5(2) - 8
3(4) + 10 - 8 =
12 + 10 - 8 =
22 - 8 =
14
- - - - - - - - - - -
3x² + 5x - 8
3( - 3)² + 5(- 3) - 8
3( 9) + (- 15 ) - 8 =
27 - 15 - 8 =
27 - 23 =
4
- - - - - - -
3x² + 5x - 8
3(.62)² + 5(.62) - 8 =
3(0.3844) + 3.1 - 8 =
1.1532 + 3.1 - 8 =
4.2532 - 8 =
-3.7468
- - - - - - - - - - - - - - - - -
4x - 3x² + 2x - x²
- 3x² - x² + 4x + 2x
-4x² + 6x
2x( - 2x + 3)
- - - - - - - - - -- - - -
5 x 6² - 5 x 3² / 3 + 2
5 x 36 - 5 x 9 / 5
180 - 45 / 5
135 / 5
27
The answer is 27
- - - - - - - -s-
2006-11-12 07:30:50
·
answer #7
·
answered by SAMUEL D 7
·
0⤊
1⤋
1.
a) 12+10-8 = 14
b) 18-15-8 = -5
c) 0.124 +3.1-8=-7.776
2. 2x sq +2x
3. ((5*36)- (5*15))/5
=(180-75)/5
= 105/5 = 21
2006-11-12 06:00:40
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
hi buddy this an trouble-free question in accordance with linear equations you should use transposition approach in this technique whilst a term is transfered from one area to different its sign turns into opposite answer: x+4-7x=22 =4-7x=22-x (right here x comes from the left area its sign adjustments) =4=22-x+7x(right here 7x comes from the left area its sign adjustments) =4-22=6x(comparable) =-18=6x x=-18/6 =-3 Bye Bye!!!!!!!!!!!!!!!!!!!!!!
2016-10-21 23:20:47
·
answer #9
·
answered by itani 4
·
0⤊
0⤋
Don't cheat do yourown work or ask your teacher
2006-11-12 07:50:52
·
answer #10
·
answered by che-che 2
·
0⤊
1⤋